Pembuatan Aplikasi Penjualan untuk Toko Furniture Berbasis Android - Christian Adiputra; Andreas Handojo; Ibnu Gunawan (Jurnal Infra, 2015)
Furniture a usual term that has been used for household needs which can be used for storing items, place to sit, place to sleep and place to do something like tables or something that its surfaces can hold things. Because of so many kinds of furnitures have made many furniture stores demands for a bigger space. This has caused for many furniture stores that doesn’t have much space, not able to display all of their products. As a result stores made products catalog every week or month. Obviously, this made the store have to spent more costs. Based on that circumstances this application was made as a shopping catalog and a shopping cart. This application is Android based, considering it’s function beside a mobile phone , it has many modern function such as its wifi and its camera for barcode scanning that can be connected to the company database Server. The application that has been made, have some list of features such as product search that can be used by accessing the Server through wifi, giving the information of ongoing promos, can do product barcode scanning with the mobile device camera, can act as a shopping cart to contain the list of products, and can send the shopping list to the Server, so that we can do the transaction later with ease.